Drought Resistance Of Several Local Upland Rice Genotypes (Oryza sativa L.) From West Sumatra Province - Diah Permata Sari; Irfan Suliansyah; Auzar Syarif (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
Rice is a major staple food for the Indonesian population, therefore, its productivity must be improved to accomplish the domestic consumption. Efforts to increase rice production in a sustainable manner in the future not only rely exclusively on lowland rice production but also from other genotypes including upland rice. West Sumatra is one of the province in Indonesia that preserves various local upland rice germplasm. The characterization of local upland rice genotypes to drought stress are required in order to support the increase of national rice production. This study aims was to obtain the West Sumatra local upland rice genotypes that are resistant to drought. The drought resistance screening was carried out in three ways, namely: 1) Testing of seed resistance with Polyethylene Glycol (PEG), 2) Testing of root penetration using a wax coating, and 3) Testing of proline content. From the study, two genotypes, namely: Susun Porti and Ladungan which have good resistance to drought.